Application Database School Health Program in Primary School Level of Surabaya City - Armyade Armyade; Chatarina Umbul Wahyuni; Rachmat Hargono (Jurnal Berkala Epidemiologi, 2015)
The School Health Service (UKS) is one of the health activity units at the elementary school level. At present, the UKS program has not been able to contribute optimally in improving the health status of school-age children. This condition is caused because UKS program planning has not been based on data and information related to school-age children's health problems. This study aims to develop a UKS database application at the elementary school level. The scope of this research includes the implementation of the UKS Triad and the recording and reporting system for the UKS elementary school level Implementation Team. This type of research is Action Research. The subject of this research was the implementation team of the UKS in Public Primary School / Elementary School (SDN) of I / 240 Sutorejo Surabaya. Data analysis uses a systems approach which is a process, input, and output. An analysis of the recording system and reporting of the UKS in SDN I/240 Sutorejo found a problem that is the source of data available only in the field of health services, so the analysis cannot be based on the UKS Triad. This research resulted in a prototype of the UKS database that was developed based on the results of the analysis of the recording and reporting system that was running on the UKS in SDN 1/240 Sutorejo implementation team. The UKS database prototype produces health education information, health services, and school environmental health guidance that can be used for UKS program planning for the implementation team and at the Public health center. The use of the UKS database requires supporting facilities including maintenance management systems that aim to make the UKS program sustainable as well as monitoring and evaluating the database system.